Synthesis and Crystal Structure of a New Compound: [Ni(C16H32N4)]2?Fe(SCN)4?(ClO4)2?0.5H2O - Bi, Jian-Hong; Huang, Zi-Xian; Li, Bai-Zhong (Asian Journal of Chemistry, 2010)
The nickel(II) compound of a tetraazamacrocycle ligand (L) (5,5,7,12, 12,14 -hexamethyl-1,4,8,11-tetraazamacrocyclic crown ethers) has been synthesized and characterized by IR spectra and elemental analysis. The crystal structure of the NiL was determined by singlecrystal X-ray. The possessing parameters: a = 21.075(4)Å, b = 7.7038(13)Å, c = 16.366 (3)Å, α = 90º, β =104.870(2)º, γ = 90º, V = 2568.3(8)Å3, Z = 2, Mr = 1174.41, Dc = 1.519 Mg/m3, μ = 1.330 mm-1, F(000) = 1226, T = 293(2) K, R = 0.0356, wR = 0.0969 for 5834 reflections with I > 2s(I)